Synthesis, Spectral Characterization, in vitro Antimicrobial and Anthelmintic Evaluations of Cu(II) Complexes with a New Schiff Base - Sharma, Disha; Revanasiddappa, Hosakere D. (Orbital: The Electronic Journal of Chemistry, 2018)
Novel Schiff base ligand (E)-2-((3-(benzyloxypyridinylimino) methyl)-4-bromophenol (HL) was synthesized. Using this Schiff base ligand, two new copper(II) complexes, C1 and C2 were prepared. Analytical techniques such as IR, 1H NMR, 13C NMR, mass, UV–visible spectroscopy, molar conductivity, magnetic measurement, ESR and TGA-DTA were used to characterize the ligand HL and its copper complexes. From the ESR spectra, square planar geometry was proposed for C1 and C2. The synthesized ligand, HL along with its copper(II) complexes were subjected to test their in vitro biological efficacies against four bacterial strains Escherichia coli, Salmonella typhi, Bacillus subtilis and Staphylococcus aureus and two antifungal strains Candida albicans and Aspergillus niger. The results obtained from this work suggest that the studied metal complexes are very effective in biological activities than its ligand. The anthelmintic test of the ligand HL and copper complexes against earthworms, Pheretima posthuma are also investigated. DOI: http://dx.doi.org/10.17807/orbital.v10i7.1168